2007
DOI: 10.1016/j.ygeno.2007.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Nine-amino-acid transactivation domain: Establishment and prediction utilities

Abstract: Here we describe the establishment and prediction utilities for a novel nine-amino-acid transactivation domain, 9aa TAD, that is common to the transactivation domains of a large number of yeast and animal transcription factors. We show that the 9aa TAD motif is required for the function of the transactivation domain of Gal4 and the related transcription factors Oaf1 and Pip2. The 9aa TAD possesses an autonomous transactivation activity in yeast and mammalian cells. Using sequence alignment and experimental dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
174
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(182 citation statements)
references
References 54 publications
6
174
2
Order By: Relevance
“…Bioinformatical analyses of the N-terminal sequences, predicted that there is a 9-amino-acid transactivation domain (9aa TAD) within the specific 15 N-terminal amino acids (MAVQSVLQL) of MKL1_S. 9aa TADs have been described as the smallest known denominator in the transactivation domains of a variety of transcription factors, ranging from yeast to mammals (Martin, 2009;Piskacek et al, 2007). Owing to the fact that the border between the isoform-specific parts and the shared sequence lies within this motif, the corresponding sequence in MKL1_L (SERKNVLQL) does not fulfill the criteria for such a domain (Fig.…”
Section: The Specific Mkl1_s Transcriptional Activity Requires a Novementioning
confidence: 99%
“…Bioinformatical analyses of the N-terminal sequences, predicted that there is a 9-amino-acid transactivation domain (9aa TAD) within the specific 15 N-terminal amino acids (MAVQSVLQL) of MKL1_S. 9aa TADs have been described as the smallest known denominator in the transactivation domains of a variety of transcription factors, ranging from yeast to mammals (Martin, 2009;Piskacek et al, 2007). Owing to the fact that the border between the isoform-specific parts and the shared sequence lies within this motif, the corresponding sequence in MKL1_L (SERKNVLQL) does not fulfill the criteria for such a domain (Fig.…”
Section: The Specific Mkl1_s Transcriptional Activity Requires a Novementioning
confidence: 99%
“…A study in 2011 found that the TP53 proline mutation did have a profound effect on pancreatic cancer risk among males [9]. A study of Arab women found that proline homozygosity at TP53 codon (72) is associated with a decreased risk for the breast cancer [10] [11] [12]. One study suggested that TP53 codon 72 polymorphisms, p53 mutation still the most common genetic change named in human neoplasia.…”
Section: Introductionmentioning
confidence: 99%
“…The site of interaction between the KIX domain and both p53-TADs corresponds with the annotated 9aaTADs and the TAF9 binding site (NMR data, eight out of nine annotated amino acids). Despite the unrecognizable sequence similarity (Table 2 and 3) 4,7 , both p53-TAD1 and p53-TAD2 share the same docking sites on the KIX domain, which may result from the presence of a common motif in the p53 transactivation domains, the 9aaTAD 8 . p53 and further well characterized 9aaTAD-transcription factors, which interact with CBP-p300 and other general co-activator GCN5 are listed in Table 3.…”
mentioning
confidence: 99%
“…None or extremely poor similarities were reported among the transactivation domains in general. Despite the enormous natural diversity, it was possible to generate a pattern and composition rules for 9aaTAD 8 . The establishment of 9aaTAD, its initial pattern and composition definition, identification and annotation (prediction correlated to experimental data) should streamline the investigations in gene regulation by transcription factors and the involvement of multiple transcriptional co-activators.…”
mentioning
confidence: 99%
See 1 more Smart Citation